The impact of China’s digital economy industry development and its structural indicators on carbon emission intensity - Wang, Yitong; Yuan, Yongke; Qian, Xiao; Chi, Yuanying (Frontiers in Environmental Science, 2024)
The development of the digital economy has reshaped the mechanisms of macroeconomic operations and had a profound impact on industrial economics. The article starts from the perspective of industrial organization theory. Based on the data of Input-output Tables with extended tables of 30 provinces, this paper analyzes the industrial development of digital economy and its three structural variables: digital manufacturing industry, digital service industry, and the development of industrial digitization on carbon emission intensity. The empirical results show that:(1) at the national level, the development of China's digital economy industries has a suppressive effect on carbon emission intensity; (2) in terms of spatial effects, the development of digital economy has significant carbon spillover effects, but digital industrialization and industrial digitization present different spatial effect results; (3) from the analysis of regional heterogeneity, in the northeast, central and western regions, the direction of influence of digital industrialization and industrial digitalization on carbon emission intensity is consistent; in the eastern region, the development of digital industrial service sector and industrial digitalization has a suppressive effect on carbon emission intensity, while digital industrial manufacturing sector presents a pro-increasing effect; (4) in terms of non-linear relationship, the impact of digital industry development on carbon intensity has a "promoting and then inhibiting" effect. The impact of digital industry development on carbon intensity shows the effect of "promoting increase, then suppressing, then promoting increase", and overall, China's digital economy industry has entered the low carbon development stage.